Anxiety, Mental Stress, and Sudden Cardiac Arrest: Epidemiology, Possible Mechanisms and Future Research - Batelaan, Neeltje M.; Seldenrijk, Adrie; van den Heuvel, Odile A.; van Balkom, Anton J. L. M.; Kaiser, Antonia; Reneman, Liesbeth; Tan, Hanno L. (Frontiers in Psychiatry, 2022)
Sudden cardiac arrest (SCA) is a leading cause of mortality and morbidity in affluent societies, which underscores the need to identify persons at risk. The etiology of SCA is however complex, with predisposing and precipitating factors interacting. Although anxiety and mental stress have been linked to SCA for decades, their precise role and impact remain unclear and the biological underpinnings are insufficiently understood. In this paper, we systematically reviewed various types of observational studies (total n=20) examining the association between anxiety or mental stress and SCA. Multiple methodological considerations challenged the summarizing and interpretation of the findings. For anxiety, the overall picture suggests that it predisposes for SCA in physically healthy populations (unadjusted OR = 2.44; 95% CI: 1.06-5.59; n=3). However, in populations at risk for SCA (n=4), associations were heterogeneous but not significant. Anxiety may partly predispose to SCA by contributing to other risk factors such as cardiovascular disease and diabetes mellitus via mechanisms such as unhealthy lifestyle and metabolic abnormalities. Mental stress appears to precipitate SCA, presumably by more directly impacting on the cardiac ion channels that control the heart’s electrical properties. This may lead to ventricular fibrillation, the arrhythmia that underlies SCA. To advance this field of research, experimental studies that unravel the underlying biological mechanisms are deemed important, and most easily designed for mental stress as a precipitating factor because of the short timeframe. These proof-of-concept studies should examine the whole pathway from the brain to the autonomic nervous system, and eventually to cardiac ion channels. Ultimately, such studies may facilitate the identification of persons at risk and the development of novel preventive strategies.